Observation of two zeros of the real amplitude in pp scattering at LHC energies - Anderson Kendi Kohara (European Physical Journal C: Particles and Fields, 2023)
Abstract Elastic scattering of charged hadrons is described by the combination of nuclear and Coulomb amplitudes. It is well know that at the very forward range the nuclear real and Coulomb parts interplay a crucial role in the determination of the magnitude of the real part at $$|t|=0$$ | t | = 0 . However, beyond $$|t|=0$$ | t | = 0 the real and imaginary nuclear amplitudes have different t dependencies and we show that at LHC energies the zeros formed by the combination $$T_C(t)+T_R^N(s,t)=0$$ T C ( t ) + T R N ( s , t ) = 0 in pp process can be potentially observed when the background due to the imaginary part is removed. This observation constrains the real part at this forward range.